Factors Influencing Parental Decisions on Respiratory Syncytial Virus Immunoprophylaxis - Shedlock, Katherine E.; Hicks, Steven D.; Gardner, Ruth E.; Kaye, Leah D.; Lipsett, Brody J.; Schaefer, Eric W.; Paul, Ian M.; Fogel, Benjamin N. (Journal of pediatrics. Clinical practice, 2025)
New respiratory syncytial virus (RSV) immunizations for infants and pregnant mothers recently became available to prevent severe RSV disease in infants. We aimed to determine the primary reasons for parental RSV immunization decisions. We further sought to evaluate the associations between vaccine receipt and source of health care information and trust in one's health care provider. A convenience sample of parents and guardians of infants were surveyed during the 2023-2024 RSV season in one newborn nursery and three affiliated clinics that are part of an academic health system. Among the 118 respondents, 79 (66.9%) chose to receive an RSV vaccine themselves (n = 42) or consented for infant immunization (n = 37). Thirty-nine (92.9%) parents who consented to maternal vaccination and 35 (87.5%) who consented to infant immunization stated a primary reason was protection for their infant. Among those that did not receive the maternal vaccine, the most common reasons were nonavailability (39.7%) or no provider immunization offer (22.2%). Infant immunoprophylaxis was most commonly refused due to the immunization being too new (66.7%). There were no significant associations between vaccine receipt and reported source of health information or between vaccine receipt and degree of trust in the health care provider. The desire to protect their infant from illness was the primary reason for parental RSV immunization intent, while the primary reasons for not immunizing were lack of availability, lack of provider recommendation, and the perception that the immunizations are too new. Ensuring availability and strong recommendations may improve immunization uptake. •Most common reason for parental RSV immunization interest is infant protection.•Provider recommendations for RSV immunizations are very influential.•Parents are more concerned nirsevimab is too new compared to maternal RSV vaccine.